Cardiovascular complications and outcomes among athletes with COVID-19 disease: a systematic review - Alosaimi, B.; AlFayyad, I.; Alshuaibi, S.; Almutairi, G.; Alshaebi, N.; Alayyaf, A.; Alturaiki, W.; Shah, M. A. (BMC Sports Science, Medicine and Rehabilitation, 2022)
Background Current evidence still emerging regarding the risk of cardiovascular (CV) sequel associated with coronavirus disease 2019 (COVID-19) infection, and considerable replicated studies are needed to ensure safe return-to-play. Therefore, we aimed in this systematic review to measure the prevalence of CV complications suffered by COVID-19 athletic patients, explore the outcomes, optimal approaches to diagnoses, and safe return-to-play considerations.